Dendritic right/left asymmetries in the neurons of the human hippocampal formation: a quantitative Golgi study Assimetrias dendríticas direita/esquerda nos neurónios da formação do hipocampo humano: estudo quantitativo Golgi - Maria José Sá (Arquivos de Neuro-Psiquiatria, 2007)
OBJECTIVE: To search for right/left asymmetries in the dendritic trees of the neuronal populations and in the cell-free layer volumes of the human hipoccampal formation. METHOD: In necropsic material obtained from six male individuals we performed a quantitative Golgi study of the dendritic trees of dentate granules, CA3 and CA1 pyramidal neurons and a volumetric analysis of dentate gyrus molecular layer, strata oriens plus alveus and strata lacunosum-moleculare plus radiatum of CA3 and CA1 fields. RESULTS: We found inter-hemispheric asymmetries in the dendrites trees of all neurons, reaching the significant level in the number of granule cells dendritic segments (higher in the left than in the right hemisphere), dendritic branching density of CA3 pyramidal cells and mean dendritic length of CA1 apical terminal segments (higher in the right than in the opposite side). No volumetric differences were observed. CONCLUSION: This study points to different anatomical patterns of connectivity in the hippocampal formations of both hemispheres which may underlie functional asymmetries. OBJETIVO: Pesquisar a existência de assimetrias direita/esquerda nas arborizações dendríticas neuronais e nos volumes das camadas não celulares da formação do hipocampo humano. MÉTODO: Efectuamos estudo quantitativo Golgi das arborizações dendríticas dos grânulos da fascia denteada e das células piramidais de CA3 e CA1, e uma análise estereológica dos volumes da camada molecular da fascia denteada, do strata oriens + alveus e do strata lacunosum-moleculare + radiatum de CA3 e de CA1 em material necrópsico colhido em 6 indivíduos do sexo masculino. RESULTADOS: Encontrámos assimetrias inter-hemisféricas nas arborizações dendríticas de todos os neurónios, significativas no número de segmentos dendríticos das células granulares (maior à esquerda do que à direita) na densidade de ramificação dendrítica das pirâmides de CA3 e no comprimento dendrítico médio dos segmentos apicais terminais das pirâmides de CA1 (maiores à direita do que à esquerda). Não encontramos diferenças volumétricas. CONCLUSÃO: Estes resultados alertam para diferentes padrões anatómicos de conectividade nas formações do hipocampo de ambos os hemisférios que podem fundamentar assimetrias funcionais.